The Rescaling of Economic Governance: Insights into the Transitional Territories of England. (August 2014) - Pemberton, Simon; Morphet, Janice
The development of functional economic areas and their relationship to governance has been attracting considerable attention. New forms of sub-regional governance have emerged that have been interpreted in a variety of ways. Within this context, a different approach to multiscalar governance linked to economic space is emerging at a European level in relation to the implementation of the Lisbon Treaty. This is embedding the principles of subsidiarity/territorial cohesion within member-states, and with sub-state scales of working being promulgated. This paper adds to existing discussions of city-regionalism by providing an alternative—yet fundamental—insight into these reform constructs within England in its relations with the EU. It explores: the role of economic spaces in the genealogy of rescaling tendencies; their co-option of governance as a 'strategic' mechanism for growth; and the emergent geo-politics associated with new sub-state governance structures and their effectiveness as intended 'transitionary' arrangements.